2018
DOI: 10.1007/s12275-018-8114-3
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence between iron acquisition and biofilm formation in Pseudomonas aeruginosa

Abstract: Bacterial biofilms remain a persistent threat to human health-care due to their role in the development of antimicrobial resistance. To combat multi-drug resistant pathogens, it is crucial to enhance our understanding of not only the regulation of biofilm formation, but also its contribution to bacterial virulence. Iron acquisition lies at the crux of these two subjects. In this review, we discuss the role of iron acquisition in biofilm formation and how hosts impede this mechanism to defend against pathogens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(79 citation statements)
references
References 122 publications
1
78
0
Order By: Relevance
“…Among the proteins downregulated in 72 h biofilms, three are associated with the iron acquisition; isochorismate synthase (MPAO1_03800), a rate-limiting enzyme involved in the production of salicylate (precursor of the siderophore pyochelin) 53 , the siderophore receptor MPAO1_23930 (PuiA), and the siderophore-interacting protein MPAO1_15475. Iron acquisition is deemed necessary for P. aeruginosa biofilm formation 54 so their down-regulation was unexpected, however, this response is likely circumvented by the utilization of alternative iron acquisition strategies including the high-affinity siderophore pyoverdine.…”
Section: Resultsmentioning
confidence: 99%
“…Among the proteins downregulated in 72 h biofilms, three are associated with the iron acquisition; isochorismate synthase (MPAO1_03800), a rate-limiting enzyme involved in the production of salicylate (precursor of the siderophore pyochelin) 53 , the siderophore receptor MPAO1_23930 (PuiA), and the siderophore-interacting protein MPAO1_15475. Iron acquisition is deemed necessary for P. aeruginosa biofilm formation 54 so their down-regulation was unexpected, however, this response is likely circumvented by the utilization of alternative iron acquisition strategies including the high-affinity siderophore pyoverdine.…”
Section: Resultsmentioning
confidence: 99%
“…Iron availability has been shown to both positively and negatively regulate bio lm formation through complex network systems 55 . Although high Fe can lead to ROS production, Kang and Kirienko suggested that iron uptake and homeostasis is essential for successful bio lm formation in Pseudomonas aeruginosa 56 . Fe-storage proteins bacterioferritin (Bfr) and ferritin A (Ftn), required to prevent ROS generation via Fenton reaction and DNA damage, are functionally very large proteins with a core to accommodate 3000 Fe atoms.…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been observed that the availability of iron greatly influences the ability of UPEC to form biofilms on the abiotic surface in urine medium (a poor source of iron); interestingly, this phenomenon was also dependent on the yersiniabactin system (Hancock et al, 2008). Second, Pseudomonas aeruginosa uses exopolysaccharides to sequester and store iron and stimulate biofilm formation (Yu et al, 2016;Kang & Kirienko, 2018). Negatively charged exopolysaccharides chelate Fe 3+ and Fe 2+ in the vicinity of the bacteria and allow its capture.…”
Section: Iron Capture and Biofilm Formationmentioning
confidence: 99%